Pemberdayaan Lokasi Wisata Datae dalam Meningkatkan Pendapatan Asli Daerah di Kabupaten Sidenreng Rappang - Sofyan B Sofyan B (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
This research was aimed to determine the empowerment of Datae’s tourism site in improving the local revenue of Sidenreng Rappang Regency. In addition, this research would also determine the influencing factors. This research was a design of descriptive-qualitative, with the intention just to give a description of ​​ Datae’s tourist site empowerment in improving the local revenue. This research also used direct survey method. The methods used to collect data were direct observation, interviews, and questionnaires to selected respondents. The sampling methods used was total sampling to take all 65 people or the entire population. The results were of the following, cultural factors was good by scoring 56,92% rate, contributing factors was sufficient at 69,23%, and motivation factor was good at 60%. The next factor was the communication which gained 73,85% for maximum answer, and the latter was a the knowledge factor which scored 60% to consider as adequate. Those results indicated a good category of Datae’s tourist site empowerment in improving the local revenue of Sidenreng Rappang Regency.